ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PERUSAHAAN DI SEKTOR KEUANGAN - KURNIA SANTOSO, FELISIANE (Berkala Ilmiah Mahasiswa Akuntansi)
Financial statement is very important for a company in reporting the results of its performance during a given period. One of the objectives of financial reporting is to ensure that financial statement can be useful to the users. In addition to the financial statements, the users also need an audit report to see the reasonableness of a company's financial statements. The time difference between the closing date until the date of issuance of the company independent auditors' report known as the audit delay. This study aims to examine the factors that affect audit delay include the size of the company, profitability, debt to equity ratio, contingency, the size of the Firm, and the auditor's opinion. Design research is quantitative and the research object is financial sector companies that listed at Indonesia stock exchange in 2008-2010. The samples used in research as much as 66 financial sector companies chosen by purposive sampling technique. Data sources obtained from the Indonesia stock exchange. Data analysis is performed by multiple linear regression analysis. The results showed that the firm size is the only variable which significantly negative effect on audit delay. Meanwhile, the five other variables had no significant effect on audit delay.